ANALISIS PENAMBAHAN KELOMPOK KERJA DAN JAM KERJA (LEMBUR) TERHADAP WAKTU PENYELESAIAN ITEM PEKERJAAN DAN BIAYA ITEM PEKERJAAN - Malelak, Ridho Abner; Usboko, Gregorius Paus; Lulu, Laurensius (Eternitas: Jurnal Teknik Sipil, 2024)
Overcoming the problem of time delays requires handling using proven methods or alternatives such as adding work groups or adding working hours. Adding working hours and labor is usually used as a solution to speed up the completion time of a project because by adding working hours, the time that can be used to work increases so that the resulting production increases and the completion time. Adding working groups and working hours to the selected work items from the critical path, namely Class A Aggregate Foundation Layer, Wearing Layer Laston and Fc 15 mpa Concrete Structure produces a new minimum production so that the completion time of the three work items is reduced, but also increases the costs required to complete the work items. Adding Working Hours (Overtime) to the three work items on the critical path, the first hour of completion duration is reduced by 12.5% in the completion duration of the work item, the 2nd hour by 22.22% in the work item, the 3rd hour by 30% in the work item. While the cost of Class A Aggregate Foundation Layer, the 1st working hour cost is 0.15%, the 2nd hour is 0.31%, the 3rd hour is 0.31%. In the Wear Layer Laston work item, the cost is 0.08% in the 2nd hour, 0.16% in the 3rd hour and 0.16%. In the fc 15 Mpa Concrete structure work item, the 1st working hour is 2.01%, the 2nd hour is 4.01% and the 3rd hour is 4.01%. The addition of labor groups for the Class A Aggregate Foundation Layer work item, the duration is reduced by 32%, the Wear Layer Laston work item is 13%, and in the Fc 15 Mpa Concrete Structure work item is 50%. The cost of the Class A Aggregate Foundation Layer work item increased by 0.37%, the Wearing Layer Laston work item increased by 8.03% and the fc 15 Mpa Concrete Structure work item did not experience an increase.